Correlation of ABO blood groups with treatment response and efficacy in infants with persistent pulmonary hypertension of the newborn treated with inhaled nitric oxide - Yi Guan; Ya Jin; Yongxue Lu; Dang Ao; Pingjiao Gu; Jiyan Yang; Guosheng Liu; Shasha Han (BMC Pregnancy and Childbirth, 2023)
Abstract Objective Not all infants with persistent pulmonary hypertension of the newborn (PPHN) respond to inhaled nitric oxide (iNO) therapy, as it is known to improve oxygenation in only 50% to 60% of cases. In this study, we investigated whether ABO blood groups were a relevant factor affecting the improvement of oxygenation by nitric oxide (NO) therapy in infants with PPHN. Methods This study was a retrospective, multicenter, and cohort-controlled trial that involved 37 medical units. Infants with PPHN who met the inclusion criteria and were treated with NO (a vasodilator) alone from July 1, 2015, to June 30, 2020, were selected and assigned into three groups: blood type A, blood type B, and blood type O (there were only 7 cases of blood type AB, with a small number of cases, and therefore, blood type AB was excluded for further analysis). The response to iNO therapy was defined as an increase in the ratio of the partial pressure of arterial oxygen (PaO2)/fraction of inspired oxygen (FiO2) > 20% from the basal value after treatment. Oxygenation was assessed mainly based on the two values, oxygenation index (OI) and PaO2/FiO2. The correlation of ABO blood groups with responses to iNO therapy and their influence on the efficacy of iNO therapy was analyzed based on the collected data. Results The highest proportion of infants with PPHN who eventually responded to iNO therapy was infants with blood type O. Infants with blood type O more readily responded to iNO therapy than infants with blood type B. Oxygenation after iNO treatment group was optimal in the blood type O group and was the worst in the blood type A group among the three groups. Infants with blood type O showed better efficacy than those with blood types A and B. Conclusion ABO blood groups are correlated with responses to iNO therapy in infants with PPHN, and different blood groups also affect the efficacy of NO therapy in infants with PPHN. Specifically, infants with blood type O have a better response and experience the best efficacy to iNO therapy.